PENGARUH SISTEM INFORMASI AKUNTANSI, SISTEM PENGENDALIAN INTERNAL, DAN PENGETAHUAN PENGURUS TERHADAP KINERJA KOPERASI (Studi Empiris pada Koperasi di Kabupaten Bantul) - Khoirunnisa Nuraini Putri Sari; Agus Purwanto (Diponegoro Journal of Accounting, 2022)
The research based on decrease the number of consumption cooperatives in Bantul Regency during the last 5 years, form 2015 – 2020. The cooperatives are considered unnormal so their activities stopped. One of the aspects in assessing the rating of cooperatives is financial aspect of the cooperatives. The purpose of this research to analyze the influence between accounting information systems, internal control systems, management knowledge to the cooperative’s performance. This research used quantitative methods and data was collected by using a questionnaire and analyze by using the SPSS 26. Respondents of this research are 56 people from 56 consumption cooperatives in Bantul Regency. The result of this research is that the accounting information systems and management knowledge have no significant effect on the cooperative’s performance. While the internal control systems has significant influence to the cooperative’s performance.